Investigating characteristics of the nonrecidivating psychopathic offender - Burt, Grant N. (Criminal justice and behavior, 2016)
Psychopathic offenders are at higher risk to violently reoffend than nonpsychopathic offenders; however, about one in four psychopathic offenders are not reconvicted for a violent offense even over extended follow-ups. The characteristics of nonrecidivating psychopathic offenders (NRPs) remain underexamined. In a sample of 123 offenders with a minimum Hare Psychopathy Checklist?Revised (PCL-R) score of 25, community follow-up of 5 years, and 4 months in a violence reduction program, 65 men receiving a violent conviction within 5 years (recidivating psychopathic offenders [RPs]) were compared with 58 who had not (NRPs). Comparatively, NRPs were older at release, had better community support, and were rated lower violence risk. NRPs also had significantly lower PCL-R Factor 2 scores, but higher Factor 1 scores. Post hoc analyses revealed prominent NRP characteristics included exploitative personality traits and a predilection for instrumentally violent crimes. Findings are discussed in terms of their implications for the risk assessment and treatment of psychopathic offenders.